THE CONCEPTS OF NEW NORMAL UNIVERSITY & HOW TO DESIGN NEW NORMAL SOCIAL MEDIA: EXTRAORDINARY CASE-COVID 19 - Gamayanto, Indra; wibowo, sasono; Sirait, Tamsir Hasudungan (Jurusan Seni dan Desain, Fakultas Sastra, Universitas Negeri Malang, 2022)
Abstract: The spread of COVID 19 has already taken place globally, and it is still stopping transmission by doing social and physical distancing. One of the affected sectors is Education. Therefore, Education must undergo drastic changes in the teaching and learning process and create high flexibility and adaptation to current conditions. This article focuses on creating a concept and innovation in the teaching and learning process, especially at the university level. It starts with the standard university concept, which consists of the fundamental knowledge, the fundamental invisible and visible experience, the fundamental innovative invisible and visible expertise, which produces the university's maturity level (the seven stages of university). This concept was later developed into a new normal university to deal with the current situation, namely the teaching and learning process that can provide solutions. Problems such as not being able to do the teaching and learning process face-to-face and others are essential factors that have an immediate address. However, the teaching and learning process can run effectively and efficiently. This study's final results are three primary things: health protocol, process protocol, monitoring, and feedback protocol, called the three stages of a new regular university. This article will also produce a new normal social media, the initial design for a social media application to help people affected by the pandemic. Keywords: COVID 19, New Normal University, Process; Systems, Technology, The Concepts Abstrak: Penyebaran COVID 19 sudah terjadi secara global, dan sampai pada hari ini masih dilakukan social dan physical distancing secara ketat. Salah satu sektor yang terkena dampak adalah Pendidikan. Oleh karena itu, Pendidikan harus mengalami perubahan signifikan dalam proses belajar mengajar dan menciptakan fleksibilitas serta adaptasi yang tinggi terhadap situasi dan kondisi saat ini. Artikel ini berfokus pada penciptaan konsep dan inovasi dalam proses belajar mengajar, khususnya di tingkat universitas. Dimulai dengan konsep standar universitas, yang terdiri dari dasar pengetahuan, dasar pengalaman yang tidak terlihat dan terlihat, dasar keahlian yang tidak terlihat dan terlihat serta inovatif, yang dimana menghasilkan tingkat kedewasaan universitas (tujuh tahap universitas). Lebih jauh lagi, konsep ini kemudian dikembangkan menjadi new normal university untuk menghadapi situasi saat ini, yaitu proses belajar mengajar yang dapat memberikan solusi. Masalah seperti tidak bisa melakukan proses belajar mengajar secara tatap muka dan lain-lain merupakan faktor penting yang harus segera diatasi. Proses belajar mengajar dapat terus berjalan dengan efektif dan efisien. Hasil akhir penelitian ini adalah tiga konsep: protokol kesehatan, protokol proses, protokol pemantauan, dan protokol umpan balik, yang disebut tiga tahap universitas reguler baru. Artikel ini juga akan menghasilkan media sosial new normal yang merupakan desain awal dalam memproduksi aplikasi media sosial untuk membantu masyarakat yang terdampak pandemi. Kata kunci: COVID 19, New normal university, Proses, Sistem, Teknologi, Konsep